Penerapan Pendekatan Struktural Think-Pair-Share (TPS) dalam Upaya Peningkatan Hasil Belajar dan Aktivitas Siswa SMA Negeri 1 Tellu Limpoe - Akmal, . (Fakultas MIPA UNM, 2010)
This research was a Classroom Action Research which intended to know whether the application of Structural Think Pair Share (TPS) approach could improve the activitity and study result of the students of X-C at SMA Negeri 1 Tellu Limpoe Kabupaten Sidenreng Rappang. The subjects of the research were 38 students of SMA Negeri 1 Tellu Limpoe Kabupaten Sidenreng Rappang which consist of 24 female and 14 male. The outcomes showed that the application of Structural Think Pair Approach was able to improve the activity and the study result of tha students. The achievement average of the students was 78,72% with 94,73% as the complete score. Besides , there was also improvement to 68,6% of the students activity.